Cultural Tradition Management and Sustainable Tourism: A Qualitative Descriptive Analysis of Caos Dahar - Ratih Titik Haryati (Green Inflation: International Journal of Management and Strategic Business Leadership, 2026)
Cultural traditions play a vital role in sustainable tourism by shaping social values, collective identity, and long-term cultural continuity. Caos Dahar, a Javanese practice involving communal food preparation and sharing, serves as an expression of gratitude, spirituality, and social cohesion. Despite its cultural significance, it has been rarely examined from a management perspective, particularly in relation to its integration into sustainable tourism systems. This study analyzes Caos Dahar as a form of cultural tradition management and explores its contribution to sustainable tourism. The research highlights the lack of management-oriented studies combining cultural traditions with sustainability frameworks. A qualitative descriptive approach was adopted, using secondary qualitative data from documented practices and relevant academic literature. Data were analyzed using thematic categorization and interpreted through a multi-theoretical framework, including motivation theory (ERG), social network theory, and cultural philosophy. The findings reveal that Caos Dahar functions as a managed cultural practice, involving implicit management processes such as planning, coordination, and role distribution. The tradition fulfills existential, relational, and growth-oriented needs, sustains social networks, and exhibits adaptability across various cultural dimensions. These characteristics enable Caos Dahar to contribute to the social, economic, and cultural aspects of sustainability within tourism. The study concludes that cultural traditions can be viewed as intangible strategic resources when properly managed. This research expands management and tourism studies by offering a management-oriented interpretation of cultural traditions and moving beyond outcome-based sustainability perspectives toward process-oriented cultural tradition management.